Multimodal antidepressant vortioxetine causes analgesia in a mouse model of chronic neuropathic pain - Zuena, Anna Rita (Mol Pain, 2018)
Vortioxetine is a multimodal antidepressant that potently antagonizes 5-HT3 serotonin receptors, inhibits the high-affinity serotonin transporter, activates 5-HT1A and 5-HT1B receptors, and antagonizes 5-HT1D and 5-HT7 receptors. 5-HT3 receptors largely mediate the hyperalgesic activity of serotonin that occurs in response to nerve injury. Activation of 5-HT3 receptors contributes to explain why selective serotonin reuptake inhibitors, such as fluoxetine, are not indicated in the treatment of neuropathic pain. Here, we studied the analgesic action of vortioxetine in the chronic constriction injury model of neuropathic pain in mice. Vortioxetine was injected once a day for 27 days at doses (10 mg/kg, intraperitoneally) that determine >90% 5-HT3 receptor occupancy in the central nervous system. The action of vortioxetine was compared to the action of equal doses of the serotonin-noradrenaline reuptake inhibitor, venlafaxine (one of the gold standard drugs in the treatment of neuropathic pain), and fluoxetine. Vortioxetine caused a robust analgesia in chronic constriction injury mice, and its effect was identical to that produced by venlafaxine. In contrast, fluoxetine was inactive in chronic constriction injury mice. Vortioxetine enhanced mechanical pain thresholds in chronic constriction injury mice without changing motor activity, as assessed by the open-field and horizontal bar tests. None of the three antidepressants caused analgesia in the complete Freund’s adjuvant model of chronic inflammatory pain. These findings raise the attractive possibility that vortioxetine can be effective in the treatment of neuropathic pain, particularly in patients with comorbid depression and cognitive dysfunction.